Monitoring Pediculosis Capitis in Students At Al-Muhajirin Islamic Boarding School, Cikarang Pusat, West Java, Indonesia - Anindita, Reza; Wahyu, Ega Nuraini; Perwitasari, Melania; Nathalia, Dede Dwi; Beandrade, Maya Uzia; Harahap, Nofria Rizki Amalia (UNUSA Press, 2024)
Introduction : Pediculosis capitis is a scalp hair disorder caused by an infestation of the lice of Pediculus humanus capitis. The spread of this disease is dominant in Islamic boarding school students. This disease besides causing itching and lesions on the scalp also causes loss of concentration and enjoyment of learning in children. The objective of this study was to determine the percentage of female students infested with P. humanus capitis. Methods : The design of this research is cross-sectional. The sample for this study was 41 female students of grade 7 at AL-Muhajirin Islamic Boarding School, Central Cikarang, West Java. Examination of P. humanus capitis on all female students was carried out using the serit method. The P. humanus capitis lice found were then collected and preserved preparations were made for microscopic morphological identification. Results : The results of this study showed that from 41 samples, 36 (87.8%) students were found to be positive for P. humanus capitis. Conclusions : The conclusion from this study is that the percentage of pediculosis capitis in female students is high, so it is necessary to take countermeasures in the form of head lice medication and education about personal hygiene for class 7 female students at Al-Muhajirin Islamic Boarding School, Central Cikarang, West Java